A CONTRASTIVE ANALYSIS OF USING NOUN PHRASE IN ENGLISH AND INDONESIAN LANGUAGE BY USING YOUTUBE VIDEO - Anita Sitanggang; Artha Yuni Trimedia Situngkir; Dwira May Situmorang (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
The goal of this study is to explain the distinctions between the types of noun phrases and how they are used in English and Indonesian. This study was based on the observation that university-level students frequently make errors while adapting the grammar of their home language (L1) to that of the target language (L2), particularly when translating noun phrases (NP) from English to Indonesian. In the research process, content analysis is used. The scientific text